Invasive green algae in a western Mediterranean Marine Protected Area: interaction of photophilous sponges with Caulerpa cylindracea. (6th May 2020) - Manconi, R.; Padiglia, A.; Padedda, B. M.; Pronzato, R.
Abstract: We report on the relationships between some conspicuous Mediterranean photophilous sponge species and Caulerpa cylindracea, a non-indigenous species. A diversification of defence strategies and behaviour is highlighted in target species belonging to different orders of Demospongiae from a western Mediterranean Marine Protected Area (NW Sardinian Sea). Caulerpa cylindracea displays a strongly invasive behaviour during body colonization of the Irciniidae Sarcotragus spinosulus and Ircinia retidermata (order Dictyoceratida). These sponges possess pre-adaptive defensive morpho-functional and physiological traits enabling them to partly withstand algal invasion. Also Aplysina aerophoba (order Verongiida) seems to be able to control colonization. Successful anti- Caulerpa strategies characterize the rarely affected Crambe crambe (order Poecilosclerida). Species-specific competitive strategies are displayed at different levels of body architecture, behaviour and physiology by native sponge species. The invasion patterns on sponges, the invasion dynamics in 2016–2017 and topographic distribution of C. cylindracea on S. spinosulus confirm this algal species as a threat, with potential long-term effects on sponge assemblages. Data suggest other kinds of poorly investigated synergic stressors affecting these habitat-forming species. Defence strategies of sponge species take the form of: (1) passive deterrence by morpho-functional pre-adaptive traits as growth form, biomass amount, surface traits, and microhabitat within the sponges' aquiferous system; (2) active physiological defence, whereby the morphology/anatomy of the sponge body is adapted to control invaders, by body remodelling and regenerative processes within the aquiferous system and at the sponge surface; (3) presumed active chemical defence by exudation processes of bioactive compounds.